Walking with the words: Student motivation toward reading and studying Shakespeare's plays through rehearsal room practices. Issue 1 (2nd January 2019) - Lee, Bridget Kiger; Enciso, Patricia; Sharp, Jessica
ABSTRACT: Educators have long been challenged to support students' engagement with and comprehension of reading complex texts, including Shakespeare's plays. Rehearsal room practice (RRP) specifically integrates the rehearsal room processes used by the Royal Shakespeare Company and other ensemble-based theatre companies with active, inquiry-based learning in the classroom. Furthermore, RRP is aligned with a theory of dialogic reading. This quasi-experimental study describes the use and impact of RRPs on high school student attitudes toward reading and perceptions of the value of reading Shakespeare's plays. Students who experienced RRP while studying Shakespeare's plays were more motivated, saw Shakespeare's plays as relevant to their lives, and wanted to read additional challenging texts at the end of the program. Implications for practice are discussed.